PERBANDINGAN TINGKAT PENGETAHUAN KAIDAH DASAR BIOETIKA PADA MAHASISWA KLINIK DAN PRE-KLINIK FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Yullya Tri Utari; Dedi Afandi; Muhammad Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTKnowledge is the knowing result against the object through senses and has different levels. There are several factors that affect the knowledge levels. This study aimed to compare the knowledge levels of principle based of bioethics between clinic and pre-clinic medical student at Faculty of Medicine University of Riau. This study used a cross-sectional design with a total sample were 180 peoples. The study showed no significant differences on the knowledge levels of principle based of bioethics between clinic and pre-clinic medical student at Faculty of Medicine University of Riau (p=0.406). Similar results were also found between the knowledge levels of principle based of bioethics with academic achievement levels (p=0.102). This study showed that there are factors that affect the knowledge level so that there is no significant differences between the knowledge levels of principle based of bioethics between clinic and pre-clinic medical student at Faculty of Medicine University of Riau.Keywords: Knowledge levels, principle based of bioethics.